Fiddle Mainia : Maine's organic edible fern - Barrett, L.E.; Diket, Lin ([Hallowell, Maine ; U.S.: L.E. Barrett,], 2014)
What Mainers and others around the world refer to as the fiddlehead, or a fiddlehead green, is actually a species of fern called the ostrich fern (Matteuccia struthiopteris). It is an emerald green fern that first appears as a tight-rolled disk (the disk resembles the end of a musical instrument, similar to the fiddle and violin) and then leafs out with large green fronds that can shoot up five to six feet in height and reach twenty-five inches around. The book includes photographs of the fiddlehead fern as well as one hundred and twenty-five recipes from around the world.
Includes recipe index.
Keywords: Cookbooks; Cooking; Vegetarian cooking; Cooking (Natural foods); Cooking (Wild foods); Fiddleheads; Ferns -- Maine; Wild plants, Edible -- Maine; Wild plants, Edible -- Canada, Eastern